Republic of Madagascar : Selected Issues. (IMF Staff Country Reports; Country Report, 2015)
This Selected Issues paper presents a study on poverty in Madagascar. Madagascar is a country with general, widespread, and increasing poverty. Most of the population is extremely poor and struggling to pay for food. Madagascar has the potential to grow rapidly. It is endowed with abundant natural resources, a unique wildlife, and a young, vibrant, and rapidly growing population. Taking full advantage of the young population will require higher investment in education and healthcare. Economic inequality appears to have declined and the poorest have in fact increased their consumption. Thus, while it is true that more people are poor today than in 2001, on average those who are deepest into poverty appear to be economically better off today than in 2001. Poverty is primarily a rural challenge. An overriding majority of the population lives in rural areas and rural poverty rates are almost double those of urban areas.